Scientific Dissemination and Deforestation: an analysis on the topic Forest Fires in Ciência Hoje magazine (Research, Society and Development, 2022)
Scientific Dissemination magazines are one of the best-known ways to popularize scientific knowledge, as they bring content in a language that is more accessible to the general public. However, as many of the reports found there are written by journalists, it is deemed necessary to investigate how certain themes are being addressed. In this sense, the present study was based on analyzing how the Ciência Hoje magazine publishes the theme “Queimadas” through the categories: General Characteristics of Texts (CGT) and Theme Addressed (TA), taking into account a subject of extreme relevance, mainly in Brazil, as it is one of the countries with the highest incidence of fires and this factor can bring not only environmental, but also economic and social impacts. Through the analysis, it was possible to notice that there was not a big difference in language in the reports written by journalists and scientists and both tried to facilitate the understanding of the topic in different ways. In addition, it was noticed that most of the reports were published in 2007 and that they emphasized warning the population about the dangers of deforestation. Based on this, it is understood that the Ciência Hoje magazine brings an important theoretical contribution on the theme "Burns" for Scientific Dissemination, however, it is always necessary that there is more research focused on this theme.